Impact of remittance on domestic labour productivity in Bangladesh - Akter, S (Progressive Agriculture, 2018)
The inflow of remittances is the largest source of foreign capital to the economy of Bangladesh, which has an important contribution to Gross Domestic Product (GDP) with broader socio-economic impact. It is important to investigate the labour productivity (LP) effects of international migration and subsequent remittances inflow because, economic growth in the long run is better reflected through LP growth. Remittances can have counteractive effects on LP of the receiving countries through its interaction with labour supply and capital accumulation. We investigated the relationship between remittances and domestic LP to ascertain long run growth impact of remittances under Solow-Swan growth model using production function approach. We performed Johansen co-integration tests using data over the 1976-2014 periods. The co-integrating equation estimates suggested a positive linear relationship between remittance and LP. The findings pointed out the direct effects of remittances on LP through physical capital accumulation. The findings of the study are a vital contribution to the empirical literatures of remittances and economic growth, which is important for policy options. Progressive Agriculture 29 (1): 33-44, 2018